Effects of stochastic resonance whole-body vibration on sensorimotor function in elderly individuals—A systematic review - Rogan, Slavko; Taeymans, Jan (Frontiers in Sports and Active Living, 2023)
Introduction Due to demographic changes, falls are increasingly becoming a focus of health care. It is known that within six months after a fall, two thirds of fallers will fall again. Therefore, therapeutic procedures to improve balance that are simple and can be performed in a short time are needed. Stochastic resonance whole-body vibration (SR-WBV) may be such a procedure. Method An electronic search to assess the effectiveness of SR-WBV on balance in the elderly was conducted using databases that included CINAHL Cochrane, PEDro, and PubMed. Included studies were assessed using the Collaboration Risk of Bias Tool by two independent reviewers. Results Nine studies showing moderate methodological quality were included. Treatment parameters were heterogeneous. Vibration frequency ranged from 1 to 12 Hz. Six studies found statistically significant improvements of balance from baseline to post measurement after SR-WBV interventions. One article found clinical relevance of the improvement in total time of the “Expanded Time to Get Up and Go Test”. Discussion Physiological adaptations after balance training are specific and may explain some of the observed heterogeneity. Two out of nine studies assessed reactive balance and both indicated statistically significant improvements after SR-WBV. Therefore, SR-WBV represents a reactive balance training.